Effective Resistivity in Relativistic Collisionless Reconnection - S. Selvi; O. Porth; B. Ripperda; F. Bacchini; L. Sironi; R. Keppens (The Astrophysical Journal, 2023)
Magnetic reconnection can power spectacular high-energy astrophysical phenomena by producing nonthermal energy distributions in highly magnetized regions around compact objects. By means of two-dimensional fully kinetic particle-in-cell (PIC) simulations, we investigate relativistic collisionless plasmoid-mediated reconnection in magnetically dominated pair plasmas with and without a guide field. In X-points, where diverging flows result in a nondiagonal thermal pressure tensor, a finite residence time for particles gives rise to a localized collisionless effective resistivity. Here, for the first time for relativistic reconnection in a fully developed plasmoid chain, we identify the mechanisms driving the nonideal electric field using a full Ohm law by means of a statistical analysis based on our PIC simulations. We show that the nonideal electric field is predominantly driven by gradients of nongyrotropic thermal pressures. We propose a kinetic physics motivated nonuniform effective resistivity model that is negligible on global scales and becomes significant only locally in X-points. It captures the properties of collisionless reconnection with the aim of mimicking its essentials in nonideal magnetohydrodynamic descriptions. This effective resistivity model provides a viable opportunity to design physically grounded global models for reconnection-powered high-energy emission.